Movement regulation of handsprings on vault - Heinen, T.; Vinken, P. M.; Jeraj, D.; Velentzas, K. (Research Quarterly for Exercise and Sport, 2013)
Purpose: Visual information is utilized in gymnastics vaulting. The question remains as to which informational sources are used to regulate handspring performance. The purpose of this study was to examine springboard and vaulting table position as informational sources in gymnastics vaulting. The hypothesis tested was that the approach-run and handspring kinematics change as a function of the position of the springboard and the position of the vaulting table. Method: Kinematic parameters of 14 female expert gymnasts' approach runs and handsprings on vault were examined, while manipulating the position of the springboard, the position of the vaulting table, or both. Results: The results revealed that feet positioning during the approach run and takeoff varied predominantly as a function of the position of the springboard. The positioning of the hands on the vaulting table varied as a function of the position of the vaulting table. Furthermore, a combined manipulation of both the position of the springboard and the position of the vaulting table led to differences in feet positioning during the approach run and during takeoff, as well as to differences in hand positioning during the repulsion phase and differences in the duration of the second flight phase. Conclusions: Findings suggest that the positions of the springboard and the vaulting table are relevant informational sources in gymnastics vaulting, whereas the effect of both informational sources unfolds on different kinematic parameters. Training programs aiming to enhance gymnasts' ability to use visual information during vaulting may be fruitful in motor skill acquisition in gymnastics.